ANALISIS TOTAL FAKTOR PRODUKTIVITAS DAN PERTUMBUHAN EKONOMI SUMATERA SELATAN - Elly Suryani (Department of Development Economics, Universitas Sriwijaya, 2006)
The objectives of this study, are to find out the influence of government investment (government spending for development), investment of private sectors, work force on the growth of the economy of South Sumatera Province, to reveal the magnitude of the contribution of the Total Productivity Factors (TPF) towards the growth of the economy in the South Sumatera Province. The data this study are series data for the period of 1993–2005 about the output of (GRDP), government spending for development, private investment and work force in South Sumatera Province. Cobb - Douglas Model and then followed by the calculation of TPF. It can be concluded that the variable of government investment through spending for development in South Sumatera has a positive and significant influence on the growth of the economy in South Sumatera, and so does the variable of private sector’s investment. Whereas the variable of work force and dummy (regional autonomy) does not have a significant influence on the growth of the economy in South Sumatera. It is further revealed that the contribution of physical capital which consists of government investment (spending for development) and private sector’s investment toward the growth of the economy in South Sumatera is 1.04 percent and 2.84 percent respectively. While the contribution of TPF is only 0.17 percent. Keywords : Total Factor Productivity, Growth of the Economy